2013
DOI: 10.1021/je400542b
|View full text |Cite
|
Sign up to set email alerts
|

On the High-Pressure Solubilities of Carbon Dioxide in Several Ionic Liquids

Abstract: The solubility of carbon dioxide in nine ionic liquids (ILs), at 298 K, 313 K, and 333 K and pressures up to 9 MPa, is presented. The solubility of CO2 in the selected ILs increases with increasing pressure and decreases with increasing temperature, as expected. The effect of several different anions on the solubility of CO2 with a common 1-ethyl-3-methyl­imidazolium cation is studied in this work. The anions compared were hydrogen sulfate ([emim][HSO4]), methylsulfate ([emim][MeSO4]), methane sulfonate ([emim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 78 publications
(171 reference statements)
3
67
0
Order By: Relevance
“…First investigations of the absorption of H 2 S with the IL [EMIM][MeSO 3 ] in our working group showed that the IL can also absorb H 2 S 60. It is also known from the literature that CO 2 dissolves in this IL and thus can be removed from natural gas by absorbing 61–63. In addition, it should also be explored if the drying performance of the IL [EMIM][MeSO 3 ] is reduced in the presence of H 2 S and CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…First investigations of the absorption of H 2 S with the IL [EMIM][MeSO 3 ] in our working group showed that the IL can also absorb H 2 S 60. It is also known from the literature that CO 2 dissolves in this IL and thus can be removed from natural gas by absorbing 61–63. In addition, it should also be explored if the drying performance of the IL [EMIM][MeSO 3 ] is reduced in the presence of H 2 S and CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The rational design of the corresponding absorption system suitable for industrial scale-up purposes will require a precise knowledge of the physical equilibrium between CO 2 and the ionic liquid. A vast number of experimental works in the literature deal with CO 2 solubility in various kinds of ionic liquids at different temperature and pressure conditions [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: June 2015mentioning
confidence: 99%
“…The CO 2 loadings in conventional imidazolium‐based [BF 4 − , PF 6 − , and bis(trifluoromethylsulfonyl)imide (Tf 2 N − )] and anion‐functionalized ILs are compared in Figure , and the results show that the physical absorption of CO 2 is the main contribution in these ILs and that the CO 2 loading in [Amim][HCOO] is the highest.…”
Section: Resultsmentioning
confidence: 99%
“…TheC O 2 loadings in conventional imidazolium-based [BF 4 À ,P F 6 À ,a nd bis(trifluoromethylsulfonyl)imide (Tf 2 N À )] and anion-functionalized ILs are compared in Figure 4, [22][23][24][25][26] and the resultss how that the physical absorption of CO 2 is the main contributioni nt hese ILs and that the CO 2 loading in [Amim][HCOO]i st he highest. [9] the water content in the vapor phase is very low and can be neglected for the CO 2 -H 2 Os ystemsu nder investigation.…”
Section: Resultsmentioning
confidence: 99%